Review of soil heavy metal pollution in China: Spatial distribution, primary sources, and remediation alternatives - Wu, Yufeng; Li, Xiao; Yu, Lu; Wang, Tengqi; Wang, Jinnan; Liu, Tingting (Resources, conservation and recycling, 2022)
•Soil heavy metal pollution of South differs from North in China, widespread in scattered areas.•Heavy industry, improper agricultural practices as well as urban development in turn become sources of soil heavy metal pollution.•Physical-chemical remediation technology is suitable for heavily polluted areas.•The combined phytoremediation and microbial remediation could be the main restoration technique for application. With the development of economy, soil heavy metal pollution becomes more severe, which causes soil resource degradation and ecosystem deterioration. In this study, we present the locations with excessive contamination and analyze heavy metal polluted provinces, as well as the status and primary factors of heavy metal pollution in Guangxi, Fujian, Liaoning and Yunnan provinces, which contain the hotspots at the city level. Results indicate that the heavy metal concentration increased from north to south in China. Soil heavy metal pollution is typical in Northeast China; Also, it is widespread in southern China, with heavy metals exceeding the standard levels in Central, Southwest and South China. Heat map reveals that mineral exploitation and industrial production are the primary causes in the most severely polluted provinces, while sewage irrigation or irrational application of fertilizer is the cause in agricultural areas. Urban development in densely populated provinces has become the third main factor. In addition, transportation and household refuse are potential driving factors. Network analysis suggests combined remediation methods are widely applied to improve remediation efficiency. Among them, physical-chemical technology, chemical-biological technology and physical-biological technology occupy 27.1%, 18.9% and 10.7% in the above four provinces. In particular, combining phytoremediation and microbial remediation techniques is the main research direction in future because of its environmental friendly. In brief, our study provides accurate spatial information, primary sources and appropriate remediation alternatives for soil heavy metal pollution in China, benefiting soil resource protection and land utilization. [Display omitted]